ASSESSMENT OF THE CLEANLINESS SERVICE OF THE CITY OF OUM EL BOUAGHI: ANALYSIS OF THE CURRENT SITUATION AND DIAGNOSIS - Amina Yahia; Sandra Bousseti; Khaled Naimi (International Journal of Innovative Technologies in Social Science, 2024)
This article presents a comprehensive assessment of the cleanliness service in the city of Oum El Bouaghi, Algeria. The main objective is to analyze the current situation of waste management and identify the gaps and challenges faced by local authorities. Through a methodological approach combining field surveys, interviews with municipal officials, and the analysis of quantitative data, the study examines various aspects of the cleanliness service, including the frequency of waste collection, the efficiency of cleaning operations, and the level of citizen satisfaction. The results reveal shortcomings in the organization and management of cleanliness services, such as delays in waste collection, a lack of citizen awareness regarding waste management, and infrastructure problems. The article also proposes recommendations to improve service quality, including resource optimization, strengthening community awareness, and adopting sustainable waste management practices. In conclusion, this assessment highlights the importance of an effective cleanliness service for the quality of life of Oum El Bouaghi residents and calls for concerted action to overcome the identified challenges.